Neuroscience basics : a guide to the brain's involvement in everyday activities - Larimore, Jennifer L. (Academic Press, 2017)
Neuroscience basics: a guide to the brain's involvement in everyday activities examines how our brain works in everyday activities like sleeping, eating, love, and exercise. Many want to better understand how the brain works, but the terminology and jargon of books can be overwhelming. The book covers the basics taught in an introductory neurobiology course designed for anyone new to the neuroscience field, including non-neuroscientists. While each of the chapters explore the brain in a normal state, Neuroscience Basics also discusses disruptions of the normal state--psychosis, Alzheimer's, Parkinson's, autism, learning disorders, etc. This book breaks down the topics into language that is more accessible while making the neuroscience topics fun and relevant. Provides basic understanding of neuroscience topics that are part of everyday lifeProvides basic diagrams and descriptions of some basic anatomyExplores and explains current research in each of the chapters and topicsExamines basics that are taught in an introductory neuroscience course to provide working knowledge of how the brain works for non-neuroscientists.